The global climatic change and its impacts in Cuba. Actions for the future - Febles, Gustavo; Ruiz, Tom?s El?as (Cuban Journal of Agricultural Science, 2009)
The objective of this review is to report and contribute to a more theoretic-practical conscience about the climatic change, its characteristics, and performance worldwide, particularly in Cuba. Some suggestions are offered for the future work. The material deals with the fundamental processes and concepts about the greenhouse effect and of the harmful gases that are released to the atmosphere. The content of the United Nations Framework Convention on Climate Change and its synergy with other agreements are profiled. Data of climate and its components, sea level rise, extreme events, and others are noteworthy. Emphasis is laid on small island countries. The information from Cuba is abundant and updated. The material provides the possibilities of adaptation and mitigation of the climatic change for the future, besides the results from the agricultural researches, as well as other elements related to the effect of the climatic change on human health. It is concluded that it is better to substitute the management of the crisis by the management of risk. Key words: climatic change, Cuba, greenhouse effect gases, mitigation.